Measuring tax efficiency : a tax optimality index - Pascalis Raimondos-Møller; Alan D. Woodland (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper introduces an index of tax optimality that measures the distance of a current tax structure from the optimal tax structure in the presence of public goods. In doing so, we derive a [0, 1] number that reveals immediately how far the current tax configuration is from the optimal one and, thereby, the degree of efficiency of a tax system. We call this number the Tax Optimality Index. We show how the basic method can be altered in order to derive a revenue equivalent uniform tax, which measures the size of the public sector. A numerical example is used to illustrate the method developed.
Keywords: H41; H21; 330; tax optimality index; excess burden; distance function; Steuertheorie; Optimale Besteuerung; Excess Burden; Theorie